2020
DOI: 10.18203/2320-1770.ijrcog20203843
|View full text |Cite
|
Sign up to set email alerts
|

Fetomaternal outcome in COVID-19 infected pregnant women: a preliminary clinical study

Abstract: Background: WHO has declared COVID-19 infection a health emergency of international concern on 11th March, 2020. It is not clear whether clinical characteristics of pregnant women with COVID-19 differ from those of nonpregnant women and whether it aggravates COVID-19 symptoms and whether antiviral therapy is necessary for COVID-19 infected pregnant women.Methods: This is prospective study of 125 cases based on the compiled clinical data for pregnant women with COVID-19 between 15th April 2020 and 10th June 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 10 publications
1
15
2
5
Order By: Relevance
“…In our study, the most common symptoms at presentation was Fever among 58.7%, Cough among 76.2%, Sore throat among 87.3%, Headache among 22.2%, Vomiting among 11.1%, Drowsiness among 9.5% and Dyspnea among 4.7%. Similar findings were reported by Shah et al [21] most common symptoms at presentation were cough (61.6%) and fever (46.4%); 38.4% of pregnant patients did not present with symptoms, but most of these patients were diagnosed as having COVID-19 infection by intensive field testing and contact tracing during the initial phase of outbreak in India. FOGSI guidelines recommends that pregnant women residing in containment areas or in large migration gatherings/evacuees centre from hotspot districts presenting in labour or likely to deliver in next 5 days should be tested even if asymptomatic [22] .…”
Section: Symptomssupporting
confidence: 86%
“…In our study, the most common symptoms at presentation was Fever among 58.7%, Cough among 76.2%, Sore throat among 87.3%, Headache among 22.2%, Vomiting among 11.1%, Drowsiness among 9.5% and Dyspnea among 4.7%. Similar findings were reported by Shah et al [21] most common symptoms at presentation were cough (61.6%) and fever (46.4%); 38.4% of pregnant patients did not present with symptoms, but most of these patients were diagnosed as having COVID-19 infection by intensive field testing and contact tracing during the initial phase of outbreak in India. FOGSI guidelines recommends that pregnant women residing in containment areas or in large migration gatherings/evacuees centre from hotspot districts presenting in labour or likely to deliver in next 5 days should be tested even if asymptomatic [22] .…”
Section: Symptomssupporting
confidence: 86%
“…We were amazed to know that none of the samples came out to be positive. 1 Shah et al also studied vertical transmission and their results indicated that 16.67% neonates at birth were positive suggesting the possibility of vertical transmission which is not according to our study. 1 Claudia Fenizia from university of Milan, Italy in 2020 also analysed SARS-CoV-2 vertical transmission in 31 obstetric patients and studied viral genome on maternal and new born nasopharyngeal swab, vaginal swabs, maternal and umbilical cord plasma, placenta and umbilical cord biopsies, amniotic fluid and milk from 31 mothers.…”
Section: Resultscontrasting
confidence: 57%
“…Chest X-ray shows pneumonia in 28 (58%) cases. 1 Asymptomatic patients were 38.4% in a study by Shah et al in 2020. While our study had 96% patients asymptomatic.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations